(untitled) (Anwer Khan Modern Medical College Journal, 2014)
The present study has been carried out to find out the distribution of prenatal, perinatal and postnatal factors associated with autistic children. The study was conducted on 270 autistic children with age ranges of 3-10 years attending special schools in Dhaka city exclusively for autistic children during July ,2001 to July ,2012 .Mean age of mother was 31.78 SD± 5.94 years .Socio demographic characteristics showed 84% housewives, 37% educated up to masters level. Mean family monthly income was Tk.24,596 SD±11,464.Antenatal factors showed 42.2% mothers anemic,44.4% had H/O pre eclampsia,40% threatened abortion, 38.1% had gestational diabetes. Perinatal factors showed obstructed labor to be 64.4%.Post natal factors showed birth asphyxia to be 47.0% and neonatal jaundice 72.6% . The study showed a higher maternal age is significantly associated with autism.(p=0.007, RR=1.18,95% CI, 0.87- 1.60) and birth asphyxia is strongly associated with autism (p=0.001,OR=8.86 , 95% CI, 1.91-41.04) .The increasing prevalence of ASD`s indicates that it is multifactorial in which genetic, prenatal, social, developmental, nutritional and environmental factors play major roles. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21126 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 14-17